Entrepreneurship and competitiveness of subregions. The case of the Wielkopolska region in Poland - Olejniczak, Karolina; Dębicka, Anna (Przedsiębiorczość a konkurencyjność podregionów na przykładzie województwa wielkopolskiego w Polsce, 2019)
Selected development factors lead to increased competitiveness of countries, regions and smaller administrative units. Management of the processes creating the competitiveness of these units becomes crucial from the point of view of their long-term development The purpose of this article is to capture the relationship between entrepreneurship and competitiveness in subregions using the example of the Wielkopolska region in Poland and to examine the differences in this area between individual subregions.. The research results indicate significant differences in the development of entrepreneurship and competitiveness between the central and peripheral subregions in the Wielkopolska region. They seem to indicate the existence of feedback between ex-post competitiveness and selected entrepreneurship indicators in subregions remote from the regional center of growth and emphasize the importance of SMEs in the economies of these subregions
Biblioteka Regionalisty, 2019, Nr 19, s. 146-160
Keywords: Dolny Śląsk